Use does not wear ragged the fabric of friendship: Thinking of objects as alive makes people less willing to replace them - Chandler, Jesse; Schwarz, Norbert (Journal of Consumer Psychology, 2010)
AbstractAnthropomorphic beliefs about objects lead people to treat them as if they were alive. Two experiments test how anthropomorphic thought affects consumers' product replacement intentions. Consumers induced to think about their car in anthropomorphic terms (i) were less willing to replace it and (ii) gave less weight to its quality when making replacement decisions. Instead, they (iii) attended to (experimentally induced connotations of) the car's “warmth,” a feature usually considered relevant in the interpersonal domain. While anthropomorphic beliefs about brands are often seen as advantageous by marketers because they increase brand loyalty, similar beliefs about products may be less desirable.